FES Bike Race preparation to Cybathlon 2016 by EMA team: a short case report - Juliana Araujo Guimarães; Lucas Oliveira da Fonseca; Ana Carolina de Sousa; Miguel Eduardo Gutierrez Paredes; George Andrew Brindeiro; Antônio Padilha Lanari Bó; Emerson Fachin-Martins (PAGEPress Publications, 2017)
FES-assisted cycling has been recommended to people struggling to emerge from a disability to more functioning life after spinal cord injury. Recommendations issued by a gowing number of scientific papershas promised toimprove body composition and physical activity levels, as well as to controlinvoluntary muscle response; favoring activity and participation which break new grounds in expanding locomotion, leisure and occupational options for people with paraplegia and tetraplegia. In this report we described our experience to select and prepare a pilot to compete in the FES Bike Race modality at Cybathlon 2016 in Kloten (Zurick). He was a man, 38 years old, with a complete spinal cord injury, level T9, three years of injury. He took part in a two preparation phases lasting respectively 18 and 12 weeks each: (1st) pre-FES-cycling and a (2nd) FES-cycling. The 1st phase aimed to explore electrical stimulation response in the quadricps, hamstrings and gluteus muscles; searching for a standard muscular recruitment enable to propel the pedals of a trike. Following, in the 2nd phase, stationary to mobile FES-cycling was performed at the same time the development of the automation and control systems were being incorporated in the trike. We adapted a commercial tadpole trycicle anda pilot controlled system. Although we had planned a three session by week protocol, for reasons of term and time to finish the trike development and be prepared to compete, in the last two weeks before the Cybatlhon an intense level of exercise was maintained. After the race, we noticedinflammatory signs on the left knee which later revealed a patella fracture. The video footage analysis confirmed ithappened during the race's first lap.